2018
DOI: 10.1111/acem.13406
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Daily Posttraumatic Stress Symptoms and Pain Over the First 14 Days After Injury: An Experience Sampling Study

Abstract: Daily hyperarousal symptoms predict same-day pain severity over the acute post-injury recovery period. We also demonstrated feasibility to screen and identify patients at risk for pain chronicity in the acute aftermath of injury. Early interventions aimed at addressing hyperarousal (e.g. anxiolytics) could potentially aid in reducing experience of pain. This article is protected by copyright. All rights reserved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 63 publications
1
14
0
1
Order By: Relevance
“…A subset of participants may not complete daily assessments due to technical difficulties or a lack of interest. Studies that used texting, which is less likely to have technical difficulties relative to an application, reported similar findings (Pacella et al, in press). Those who did not complete any mobile assessments did not differ from those who did, however, which suggests there may be few differences in these groups at baseline.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…A subset of participants may not complete daily assessments due to technical difficulties or a lack of interest. Studies that used texting, which is less likely to have technical difficulties relative to an application, reported similar findings (Pacella et al, in press). Those who did not complete any mobile assessments did not differ from those who did, however, which suggests there may be few differences in these groups at baseline.…”
Section: Discussionmentioning
confidence: 61%
“…The response rate was 44.93%, which was markedly lower than that of the text messaging studies. A recent study used text messages to track PTSD and pain symptoms for 14 days after an injury (Pacella, Girard, Wright, Suffoletto, & Callaway, in press). The mean response rate was 86%.…”
mentioning
confidence: 99%
“…Finally, PTSD Coach may be better positioned for use as an adjunct or first tier within a stepped-care model to improve postinjury recovery, 37 with initial ED screening and symptom monitoring after injury to maintain communication with and identify those with high symptoms in the weeks and months to follow. 9,38,59 LIMITATIONS This pilot study had a small sample size, a limited 1month time period of suggested app use, and a limited follow-up period of 3 months postinjury, the earliest time when PTSS is considered persistent. 19 Notably, the validity of our findings, particularly those regarding group differences for black patients, is threatened by the small sample size and a lack of a priori planned analyses or sample size calculation; future research is warranted to replicate these findings using adequately powered preplanned samples.…”
Section: Usability and Acceptabilitymentioning
confidence: 99%
“…8 Even in the acute aftermath of ED care for minor injury, hyperarousal symptoms of PTSD are associated with daily pain. 9 Additionally, PTSD is prevalent and increases risk for recurrent health problems and mortality among patients seeking emergency treatment and evaluation for acute medical events such as acute cardiac syndrome (12%), 10,11 transient ischemic attack, and stroke (25%). 11 Notably, PTSD symptoms (PTSS) contribute to distress-related impairments [12][13][14][15] and poor outcomes 6,8,16 in the absence of full-blown PTSD.…”
mentioning
confidence: 99%
“…Regarding recovery after minor injury, Pacella and colleagues previously found that psychological symptoms are associated with physical symptoms among ED patients discharged home immediately from the ED; specifically, hyperarousal symptoms of PTSD are associated with daily pain during the first 14 days after injury. Similarly, patients with mild–moderate motor vehicle collision (MVC)‐related injuries report reduced health‐related QOL at 2 years post‐MVC and at least one psychiatric diagnosis (50%) at 6‐, 12‐, and 24‐months post‐MVC .…”
Section: Current Studymentioning
confidence: 99%